Biogenic synthesis of silver nanoparticles/reduced graphene oxide (AgNPs/rGO) mediated Nephelium lappaceum leaf extract as an effective solid acid catalyst for liquid-phase benzene nitration - Dewi Yuanita Lestari; Akhmad Syoufian; Poedji Loekitowati Hariani; Amalia Kurnia Amin; Won-Chun Oh; Aldino Javier Saviola; Karna Wijaya (Results in Chemistry)
Researchers are increasingly required to adopt green chemistry principles in developing nanomaterials and their applications to support a sustainable chemical industry and contribute to environmental balance. This study presents the green synthesis of AgNPs/rGO nanocomposites using Nephelium lappaceum as both a bio-reductant and a capping agent, alongside their characterization and application as a solid acid catalyst in benzene nitration reactions. Graphene oxide (GO) was synthesized from graphite using a modified Hummers method, and the AgNPs/rGO nanocomposites were prepared via an ex-situ approach. In this process, Nephelium lappaceum leaf extract served to reduce both silver ions and GO to rGO. The results revealed that the silver nanoparticles were spherical, with an average diameter of 6.76 nm, and were uniformly deposited on the reduced graphene oxide (rGO) surface. Catalyst performance tests demonstrated that the synthesized AgNPs E5/rGO catalyst achieved excellent yields and selectivity in converting benzene into nitrobenzene. Furthermore, the catalyst exhibited remarkable reusability, with only a slight decrease in yield after five uses, while maintaining consistent selectivity toward nitrobenzene as an essential and promising chemical intermediate for many derived chemicals.